Analisis Karakteristik Lalu Lintas Terhadap Tingkat Pelayanan Jalan pada Jalan Komodo, Ruteng, Kabupaten Manggarai - Karels, Dolly W.; Ramang, Ruslan; Tatus, Mariani (JURNAL FORUM TEKNIK SIPIL (J-ForTekS), 2023)
Komodo Street is a national road network that connects the regencies of Manggarai and West Manggarai. Along the Komodo Street there are several shopping centers, restaurants and houses of residents who do not have adequate parking space. The existence of pedestrians crossing and the activity of vehicles going in and out of the road affect the level of service. The purpose of this study is to determine the quantity of traffic flow, capacity, and level of service on Komodo Street. The method used in this study is the quantitative analysis based on the PKJI 2014. The analysis of the value of the maximum traffic flow at Point 1 yielded a maximum of 1.103 light vehicle units/hour and a minimum of 519 light vehicle units/hour. At Point 2, the maximum traffic flow value is 1.085 light vehicle units/hour, while the minimum value is 568 light vehicle units/hour. At Point 3, the maximum traffic flow value is 1.077 light vehicle units/hour and the minimum is 558 light vehicle units/hour. At Point 4, the maximum traffic flow value is 1.068 light vehicle units/hour and the minimum is 612 light vehicle units/hour. The maximum capacity value for Point 1 is 2.105 light vehicle units/hour, while the minimum capacity value is 2.061 light vehicle units/hour. The maximum capacity value for Point 2 is 2.105 light vehicle units/hour, and the minimum capacity value is 1.953 light vehicle units/hour. The capacity value for Points 3 and 4 is 2.105 light vehicle units/hour. The level of service values for all points vary at any time, namely B and C.